1988
DOI: 10.1159/000461753
|View full text |Cite
|
Sign up to set email alerts
|

Non-A Non-B Hepatitis and the Safety of Intravenous Immune Globulin, pH 4.2: A Retrospective Survey

Abstract: Evidence for transmission of non-A non-B hepatitis (NANB) was sought in 41 patients with primary immune deficiency who were receiving human intravenous immune globulin (IGIV) over periods ranging from 6 to 15 months at a monthly dosage of 400 mg/kg body weight. One lot of a reduced and alkylated IGIV and three lots of a nonmodified preparation stabilized at pH 4.2 were used. No evidence of NANB was found, although transient elevations in serum glutamic pyruvic transaminase (alanine aminotransferase) were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 21 publications
(26 reference statements)
2
12
0
Order By: Relevance
“…Thus, the trial confirmed that the study IVIG did not transmit hepatitis. The results agree with the outcome of some retrospective or prospective studies [9][10][11]. Our data corroborate the clinical experience with the IVIG prep aration based on this procedure (Central Laboratory of the Swiss Red Cross Blood Transfusion Service, Sandoglobulin) which is now in use for approximately 10 years.…”
Section: Resultssupporting
confidence: 90%
“…Thus, the trial confirmed that the study IVIG did not transmit hepatitis. The results agree with the outcome of some retrospective or prospective studies [9][10][11]. Our data corroborate the clinical experience with the IVIG prep aration based on this procedure (Central Laboratory of the Swiss Red Cross Blood Transfusion Service, Sandoglobulin) which is now in use for approximately 10 years.…”
Section: Resultssupporting
confidence: 90%
“…, we published our experiences in 41 sub jects receiving monthly infusions of a nonmodified IGIV, pH 4.25 (Cutter Biological) followed up to 15 months [5]. In this series of immunodeficient patients, evidence of NANBH was not found in any subject.…”
Section: In 1988 Based Upon Reports Of Transmission Of Non-a Non-b Hmentioning
confidence: 87%
“…All except 1 of the patients had participated in our previous studies. Details of the patient entry and exclusion criteria are contained in our previous paper [5],…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations